Copper-catalyzed consecutive reaction to construct quinazolin-4(3H)-ones and pyrido[2, 3-d]pyrimidin-4(3H)-ones. Issue 6 (11th February 2016) - Li, Ting; Chen, Minglu; Yang, Lei; Xiong, Zhengxin; Wang, Yongwei; Li, Fei; Chen, Dongyin
Abstract: An efficient and practical copper-catalyzed consecutive synthesis of quinazolin-4(3 H )-ones and pyrido[2, 3- d ]pyrimidin-4(3 H )-ones from easily available 2-halobenzamides (or 2-halonicotinamides), aldehydes, and sodium azide has been developed, which gave the corresponding target products in 50–95% yields for 29 examples. This remarkable consecutive process involved sequential copper-catalyzed SN Ar, reduction, cyclization, and oxidation. Notably, this work would provide a novel synthetic strategy for bioactive molecules containing quinazolinone class skeletons. Graphical abstract: